2009
DOI: 10.1103/physrevb.79.161403
|View full text |Cite
|
Sign up to set email alerts
|

Boron fullerenes: FromB80to hole doped boron sheets

Abstract: We demonstrate the existence of a family of stable boron fullerenes containing 80n 2 atoms that is related to the family of 60n 2 carbon icosahedral fullerene series and is compatible with the recently proposed stable boron sheets composed of triangular and hexagonal motifs. All electron density-functional calculations on the B 320 , B 720 , B 1280 , and B 2000 confirm their stability and show that the quantum size effects open up electronic band gaps in the boron fullerenes at B 1280 . Boron fullerenes below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 30 publications
(38 reference statements)
2
33
0
Order By: Relevance
“…1). 8 Subsequent investigations [10][11][12][13][14][15][16] indicated that the atomic buckling are particularly sensitive to the basis set employed and the level of theory used in describing exchange-correlation effects. However, recent investigation by Szwacki and Tymczak with the use of computational intensive ab-initio calculations up to second-order Møller-Plesset perturbation (MP2) theory reveals that the I h boron buckyball is the lowest energy conformation owing to the crucial importance of correlation effects.…”
mentioning
confidence: 99%
“…1). 8 Subsequent investigations [10][11][12][13][14][15][16] indicated that the atomic buckling are particularly sensitive to the basis set employed and the level of theory used in describing exchange-correlation effects. However, recent investigation by Szwacki and Tymczak with the use of computational intensive ab-initio calculations up to second-order Møller-Plesset perturbation (MP2) theory reveals that the I h boron buckyball is the lowest energy conformation owing to the crucial importance of correlation effects.…”
mentioning
confidence: 99%
“…The number of studies of new nanostructures (Zhao et al 2005;Iñiguez et al 2007;Yildirim et al 2005;Bauschlicher et al 2002;Zope et al 2009;Zhang et al 2000;Yoon et al 2008;Yang et al 2009;Lee et al 2008;Durgun et al 2008;Koh et al 2011, Kiran et al 2006 able to absorb H 2 in at least 9 wt% have increased in the last years, following the goal proposed by the US Department of Energy of developing a system with this net gravimetric capacity for hydrogen storage. Among the different materials under consideration, systems composed by C 60 compounds coated with transition metals are between the most promising ones.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on searching the lowest energy configurations has yielded a variety of stable boron structures due to electron deficient nature of boron. Such structures involve molecular wheels [1,2], boron sheets composed of triangular and hexagonal motifs [3][4][5][6][7][8][9][10][11][12], cage architectures based on empty polygons [13], crossing double rings [14,15], snub structures [8], filled hexagons [16] and filled pentagons [17,18]. Boron based forms are known for their complex chemistry.…”
mentioning
confidence: 99%